2016
DOI: 10.1016/j.jbiomech.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Impact attenuation capabilities of football and lacrosse helmets

Abstract: Although the National Operating Committee on Standards for Athletic Equipment (NOCSAE) standards are similar for football and lacrosse helmets, it remains unknown how helmets for each sport compare on drop tests. Due to the increased concern over head injury in sport and the rapid growth in lacrosse participation, it is useful to compare the performance of various football and lacrosse helmets. Therefore, the goal of this study was to document the impact attenuation properties of football and lacrosse helmets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…[13][14][15][16] In this crossover study, each of the 3 helmets was tested with and without the Guardian Caps at each of the 6 drop locations. We based our sample size on power analyses using 2 previously published studies 17,18 with similar data, which indicated that 3 helmets per group would be sensitive to differences in impact attenuation (a ¼ .05 and 1-b ¼ 0.80). The experimental design for the Riddell Speed helmets (Riddell Sports, Elyria, OH) is seen in Figure 3.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15][16] In this crossover study, each of the 3 helmets was tested with and without the Guardian Caps at each of the 6 drop locations. We based our sample size on power analyses using 2 previously published studies 17,18 with similar data, which indicated that 3 helmets per group would be sensitive to differences in impact attenuation (a ¼ .05 and 1-b ¼ 0.80). The experimental design for the Riddell Speed helmets (Riddell Sports, Elyria, OH) is seen in Figure 3.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research focused on the use of the NOCSAE standard drop test as the primary means of testing. While limited, it was used to demonstrate that football helmets dramatically outperform lacrosse helmets in the laboratory 20 and that aftermarket impact attenuation systems such as the Guardian cap provide limited decreases in the severity index. 21 In addition, Cournoyer et al 22 determined that energy absorption in football helmets changes statistically significantly after 90–100 impacts, but the effect size was not sufficient to warrant helmet replacement.…”
Section: Discussionmentioning
confidence: 99%
“…), did not include laboratory impact data, did not characterize football-specific head impact conditions, or analyzed previously collected datasets (review articles, part of research anthology, etc.). This filtering process resulted in 35 journal articles 28,10,11,1337 that met the review criteria, which are included in the data presented in this review article.…”
Section: Methodsmentioning
confidence: 99%